1993
DOI: 10.1080/02724936.1993.11747655
|View full text |Cite
|
Sign up to set email alerts
|

Acute lower respiratory tract infection in hospitalized children in Zimbabwe

Abstract: A descriptive study was undertaken to document clinical and socio-demographic features and also to identify risk factors for mortality in children hospitalized with acute lower respiratory tract infection (ALRI). A total of 704 children aged from 1 month to 5 years admitted to Harare Central Hospital were studied. The peak age group was between 1 and 6 months. Seventy per cent of the children were found to have normal nutrition and 12% severe malnutrition. Seventy-eight per cent had severe and the remainder mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
4

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 17 publications
3
19
4
Order By: Relevance
“…Acute respiratory infection treatment failures were predominantly seen in cases with cough of >14 days before admission or prior admissions for acute respiratory infection 10 or cases with very fast breathing, hypoxia, but without fever, 11,54 which are typical features of severe asthma rather than bacterial pneumonia which is characterised by fever >38.5°C. 30,31 Secondly, mortality data from low-income countries showed that RSV is an important cause of respiratory death in childhood.…”
Section: Asthma In the Under-5s: An Invisible Killer?mentioning
confidence: 99%
See 3 more Smart Citations
“…Acute respiratory infection treatment failures were predominantly seen in cases with cough of >14 days before admission or prior admissions for acute respiratory infection 10 or cases with very fast breathing, hypoxia, but without fever, 11,54 which are typical features of severe asthma rather than bacterial pneumonia which is characterised by fever >38.5°C. 30,31 Secondly, mortality data from low-income countries showed that RSV is an important cause of respiratory death in childhood.…”
Section: Asthma In the Under-5s: An Invisible Killer?mentioning
confidence: 99%
“…51 Moreover, several comparative studies showed equivalent treatment results between different types, doses, and administration forms of antibiotics in children with IMCI-defined pneumonia. [52][53][54] Treatment failures of serious pneumonia were primarily related to infants (3-11 months) with very fast breathing, chest indrawings and hypoxia 10,11,53 and long-term cough, 10 but were not associated with fever, 10,11,54 raising questions concerning the diagnosis of bacterial pneumonia according to BTS guidelines.…”
Section: Over-diagnosis Of Bacterial Pneumoniamentioning
confidence: 99%
See 2 more Smart Citations
“…It is now established that IgG2 type antibodies are the most effective against encapsulated bacteria such as Streptococcus pneumoniae, particularly in young children.s It would appear that children with low IgG2 levels would have correspondingly low levels of IgG2-type antibodies Bacterial pneumonia is the commonest cause of morbidity and mortality in Zimbabwe. 1 The children most at risk are those infected with HIV. [2][3][4] We reported, in a recent study2 that the great majority of children admitted to hospital with pneum onia have hypergam m aglobulinaem ia in immunoglobulins A (IgA), G (IgG) and M (IgM).…”
Section: Introductionmentioning
confidence: 99%